An analytical framework for strategic delta planning: negotiating consent for long-term sustainable delta development. Issue 8 (3rd August 2017) - Seijger, C.; Douven, W.; van Halsema, G.; Hermans, L.; Evers, J.; Phi, H.L.; Khan, M.F.; Brunner, J.; Pols, L.; Ligtvoet, W.; Koole, S.; Slager, K.; et al.
Abstract : Sectoral planning on water, agriculture and urban development has not been able to prevent increased flood risks and environmental degradation in many deltas. Governments conceive strategic delta planning as a promising planning approach and develop strategic delta plans. Such plans are linked to actions and means for implementation in the short-term, in line with long-term strategic choices. This paper introduces an analytical framework that focuses on the role of actors, innovative solutions and participatory planning tools in negotiating consent for the strategic choices in a delta plan and its implementation. Cases of Bangladesh, the Netherlands and Vietnam are discussed as a plausibility probe to explore the framework's potential. The probe reveals that the framework is promising to explain the process and outcomes of strategic delta planning in urbanizing deltas. The paper ends with an initial research agenda to stimulate research and discussion on this new delta planning approach.